Self-Control and Social Pressure an Important Determinant on The Saving Behaviour Among University’ Students - Haderi, Sami AL; Ishak, Khairol Anuar; Sanabani, Waddah Ismail Tawfik Al; Sanabani, Tawfik Al; ALHamdani, Adel (International Journal of Engineering and Technology, 2018)
For decades, many researchers have investigated the determinants of individual’ saving behavior of household and employees but not many on the young individuals such as students in the universities. Despite that, not many studies studied financial behavior of students in the university, the majority of studies did not drive by theory, and focused on one single factors only. Purpose: Therefore, this study aimed to explore and investigate the influence of self-control, social pressure and knowledge in financial management on the saving behavior among Malaysian students’ university by applying Planned Behavior Theory. Methodology: the research strategy for this study was survey questionnaire for collecting the primary data. The samples size comprised 340 students from University Utara Malaysia using sample random sampling technique. Descriptive, goodness of the measurements and model validation Parametric test (ANOVA) were used to analysis the saving behaviour scores of the respondents by SPSS 24th.  The result: shows that there are positive relation for self-control, social pressure and knowledge in financial management on saving behavior while the greatest impact on saving behavior was the social pressure. For practical implication, retail banks can use this research contribution to design effective strategies in order to penetrate the saving behavior of university’ young students. Besides that, it also lightens the policy’ makers in the university and government to encourage saving among the university’ students. Also, provides the parents with insights explanation to ensure foster a sound saving behavior for their children.